Digitalization of Public Services for Koperasi Merah Putih through E-Government: Platform MerahPutih.kop.id - Fauzi, Erinda Alfiani; Rosmita; Sarmito; Sirait , Mahmudin; Fatimah, Haliza; Zulfauzan, Ricky; Ul'zikri, Ahmad Robi; Masyahbandi, Rizki; kahayanto, Edi; Panjika, Yunus Praja; Hutapea, Charles (Journal of Indonesian Rural and Regional Government, 2025)
The Indonesian government, through Presidential Instruction Number 9 of 2025, has launched a program to establish 80,000 Koperasi Desa/Kelurahan Merah Putih supported by the digital platform https://merahputih.kop.id/ as an implementation of e-government in the community economic empowerment sector. This digital transformation aims to enhance transparency, accountability, and effectiveness in cooperative management throughout Indonesia through the utilization of information technology. This research is important for evaluating the readiness and effectiveness of e-government implementation in supporting the government's strategic program before its official launch on July 12, 2025. The study employs a literature review method with a qualitative descriptive approach and analyzes the platform based on Indrajit's (2006) theory of e-government implementation, which encompasses the dimensions of Support, Capacity, and Value. The research findings indicate that the MerahPutih.kop.id platform possesses very strong political and regulatory support, adequate technological infrastructure with self-declare features and a national dashboard, as well as the potential to deliver significant value in the form of enhanced transparency, administrative efficiency, and strengthening of people's economy. However, long-term success depends on the ability to overcome challenges related to the digital divide, digital literacy of rural communities, and platform management sustainability. This platform has the potential to become a successful e-government model for community economic empowerment if continuous improvements and long-term commitment from all stakeholders are undertaken.